Effect of NaCl on the Self-Aggregation of n-Octyl â-D-Thioglucopyranoside in Aqueous Medium. - Molina-Bolivar, Jose Antonio; Hierrezuelo-Osorio, José Manuel; Carnero-Ruiz, Cristóbal (ACS, 2006)
This report investigates the effect of sodium chloride (NaCl) on the micellization, surface activity, and the evolution in the shape and size of n-octyl â-D-thioglucopyranoside (OTG) aggregates. By using surface tension measurements, information was obtained on both changes in the critical micelle concentration and adsorption behavior in the air-liquid interface with the electrolyte concentration. These data were used to obtain the thermodynamic properties of micellization along with the corresponding adsorption parameters in the airliquid interface. From extended static and dynamic light scattering measurements, the micelle molecular weight, the mean aggregation number, and the second virial coefficient, the apparent diffusion coefficient and the mean hydrodynamic radius of micelles in a range of NaCl concentrations were obtained. The light scattering data have shown that when the surfactant concentration is lower to 4.5 g/L, only spherical micelles are formed. However, an increase in the surfactant concentration induces an increase in micellar size, suggesting a rodlike growth of the micelles. This deviation of micelle geometry from spherical to rodlike is supported both by the ratio between the hydrodynamic radius and the radius of gyration and by the angular dependence of light scattering. On the other hand, the studies performed in the presence of high NaCl concentration (0.2 and 0.5 M) provide strong support for the view that the micelles may overlap together to form an entangled network above certain crossover concentration.
https://v2.sherpa.ac.uk/id/publication/21299?template=romeo
Keywords: Micelas; Electrólitos; Agentes tensioactivos; Surfactants; Micelles; Electrolytes